Ehical Reading Of Platoss The Republic - Ybanez Tomacruz, Jose Ma (Bangladesh Journal of Bioethics, 2012)
The last four books of Plato’s THE REPUBLIC manifest fecundity, not simply in terms of books or pages but in terms of topics or themes. Plato in this opus, true to the form of a Socratic disciple, uses the method of the catena -chain. That is, one topic is nexated or interconnected to the other. This is also the reason why I have decided to delve into this paper not in terms of books but thematically, more specifically, those I consider to be major ones. These themes that I deem to be major ones contained in the four books are Plato’s notions of human nature and morality, socio-political philosophy, the process of education or learning, and then his epistemology. However, here I have decided to tackle only one, i.e., Plato’s notions of human nature and morality. Lastly, let it also be pointed out that all the expository work and critique shared here are all mine, and thus, for any error or shortcoming, the burden is solely mine and not of Plato nor of any other person. DOI: http://dx.doi.org/10.3329/bioethics.v1i2.9622 Bangladesh Journal of Bioethics 2010; 1(2): 2-6